Endoglin and alk1 as therapeutic targets for hereditary hemorrhagic telangiectasia. (3rd October 2017) - Ruiz-Llorente, Lidia; Gallardo-Vara, Eunate; Rossi, Elisa; Smadja, David M.; Botella, Luisa M.; Bernabeu, Carmelo
ABSTRACT: Introduction : Hereditary Haemorrhagic Telangiectasia (HHT) is as an autosomal dominant trait characterized by frequent nose bleeds, mucocutaneous telangiectases, arteriovenous malformations (AVMs) of the lung, liver and brain, and gastrointestinal bleedings due to telangiectases. HHT is originated by mutations in genes whose encoded proteins are involved in the transforming growth factor β (TGF-β) family signalling of vascular endothelial cells. In spite of the great advances in the diagnosis as well as in the molecular, cellular and animal models of HHT, the current treatments remain just at the palliative level. Areas covered : Pathogenic mutations in genes coding for the TGF-β receptors endoglin ( ENG ) (HHT1) or the activin receptor-like kinase-1 ( ACVRL1 or ALK1 ) (HHT2), are responsible for more than 80% of patients with HHT. Therefore, ENG and ALK1 are the main potential therapeutic targets for HHT and the focus of this review. The current status of the preclinical and clinical studies, including the anti-angiogenic strategy, have been addressed. Expert opinion : Endoglin and ALK1 are attractive therapeutic targets in HHT. Because haploinsufficiency is the pathogenic mechanism in HHT, several therapeutic approaches able to enhance protein expression and/or function of endoglin and ALK1 are keys to find novel and efficient treatments for the disease.